PEDAGOGICAL MODEL FOR THE DEVELOPMENT OF PROFESSIONAL COMPETENCE OF TEACHERS BASED ON DIGITAL TECHNOLOGIES (Scientific journal of the Fergana State University, 2023)
This article discusses the social significance of establishing pedagogical activities aimed at the effective use of the possibilities of digital technologies in the development of professional competence of teachers, which positively affect the quality of education in the context of digitalization of education, eliminating the human factor. factor in preventing corruption.